어떻게 12-15sqrt6 + 8sqrt6 - 10sqrt36을 단순화합니까?

어떻게 12-15sqrt6 + 8sqrt6 - 10sqrt36을 단순화합니까?
Anonim

대답:

# -48-7sqrt (6) #

설명:

# 12-15sqrt (6) + 8sqrt (6) -10sqrt (36) #

# = 12-15sqrt (6) + 8sqrt (6) -10sqrt (6 ^ 2) #

# = 12-15sqrt (6) + 8sqrt (6) -10 * 6 #

# = 12-15sqrt (6) + 8sqrt (6) -60 #

# = 12-60 + (- 15 + 8) sqrt (6) #

# = - 48-7sqrt (6) #

대답:

# -48- (7 * sqrt (6)) #

설명:

# 12 + (-15 * sqrt (6)) + (8 * sqrt (6)) + (- 10 * sqrt (36)

우리는 그것을 알고있다. #sqrt (36) = 6 #.

그래서, # 12 + (- 15sqrt (6)) + (8 * sqrt (6)) + (- 60) #.

#12-60=-48#

그래서, # -48 + (- 15sqrt (6)) + (8 * sqrt (6)) #

자, 꺼내. #sqrt (6) # 마지막 두 괄호에서.

그건 우리에게 줄거야. # -48 + (sqrt (6) * (- 15 + 8)) #

#-15+8=-7#

그래서 대답은 # -48- (7 * sqrt (6)) #